Using social network analysis for analysing online threaded discussions - Rodríguez Hidalgo, Roberto Carlos; Zhu, Chang; Questier, Frederik; Torres Alfonso, Aida María (My University, 2015)
This study analyses the use of online threaded discussions (OTD) through social network analysis (SNA). The participants involved are university students in a Cuban higher education setting. It was conducted in the Programming Technologies course of the Information Sciences, at the Universidad Central “Marta Abreu” de Las Villas (UCLV). Online discussions are part of the blended learning of this course. The social network analysis shows that online discussions reinforced student peer relationships and network dynamics. Furthermore, it is shown that SNA is a useful approach to analyze students’ peer interactions in the digital space by comparing the peer relations before OTD and those during the OTD.
Online collaboration
Keywords: Colaboración en línea; online collaboration; Online threaded discussions; Discusiones hiladas en línea; Peer relationship; Relaciones entre pares; Social networks analysis; Análisis de redes sociales